Invisibilidade, apagamento e estereótipos de povos indígenas no espaço escolar: um diálogo com Manoela e Suzana Karipuna e suas perspectivas sobre ser indígena mulher - SOARES, Ana Cláudia Dutra (Universidade Federal do Pará, 2023)
This dissertation aims to carry out a debate regarding the invisibility and historical erasure of indigenous peoples and indigenous women, the stereotyped concepts and prejudices that permeate generations and are still part of reality and everyday school life, through a debate with the indigenous Ana Manoela Primo and Suzana Primo, from the Karipuna peoples of Amapá, emphasizing that, by raising a debate about the historical invisibility of indigenous women, it is possible to bring up their situation, their struggles, reflections and violence still suffered, as well as provide a bridge with decolonial feminism and its role in understanding the Latin American context with regard to gender and race. It is a fact that the school environment is also a space for the propagation of violence, because by relegating a specific people and gender to historical clandestinity, it determines the construction of stereotypes about their culture and historical participation. The research will be carried out with the students of the 9th grade classes of the E.M.E.F. Mayor Oton Gomes de Lima, located in the city of Moju-Pa, and the work aims, in addition to carrying out a bibliographical analysis, debates with students and interviews with indigenous women to discuss their perceptions about the historical condition of the original peoples of Brazil and their respective genres.